2023
DOI: 10.3389/fnut.2023.1236417
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus reuteri DSM 17938 reverses gut metabolic dysfunction induced by Western diet in adult rats

Jumana Abuqwider,
Angela Di Porzio,
Valentina Barrella
et al.

Abstract: IntroductionMicroencapsulation of probiotic bacteria is an efficient and innovative new technique aimed at preserving bacterial survival in the hostile conditions of the gastrointestinal tract. However, understanding whether a microcapsule preserves the effectiveness of the bacterium contained within it is of fundamental importance.MethodsMale Wistar rats aged 90 days were fed a control diet or a Western diet for 8 weeks, with rats fed the Western diet divided into three groups: one receiving the diet only (W)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 79 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…It has been demonstrated that the consumption of an HF/HFr diet over 8 wk resulted in both gut dysbiosis and a change in the permeability of the gut barrier. As an effective probiotic, Limosilactobacillus reuteri DSM 17938 may be used to prevent the detrimental effects of an HF/HFr diet on the gut[ 126 ].…”
Section: Prevention and Management Of Metabolic Disordersmentioning
confidence: 99%
“…It has been demonstrated that the consumption of an HF/HFr diet over 8 wk resulted in both gut dysbiosis and a change in the permeability of the gut barrier. As an effective probiotic, Limosilactobacillus reuteri DSM 17938 may be used to prevent the detrimental effects of an HF/HFr diet on the gut[ 126 ].…”
Section: Prevention and Management Of Metabolic Disordersmentioning
confidence: 99%